1997
DOI: 10.2466/pms.1997.84.1.251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Autonomic and Respiratory Parameters of Girls after Yoga and Games at a Community Home

Abstract: The heart rate, breathing rate, and skin resistance were recorded for 20 community home girls (Home group) and for 20 age-matched girls from a regular school (School group). The former group had a significantly higher rate of breathing and a more irregular breath pattern known to correlate with high fear and anxiety, than the School group. Skin resistance was significantly lower in the School group, which may suggest greater arousal, 28 girls of the Home group formed 14 pairs, matched for age and duration of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…98,115,125,127 These trials included studies of healthy ¶ ¶ and hypertensive adults 107,123 and of healthy children. 115,141 In addition, in a cross-sectional study of healthy middle-aged men, Vyas and colleagues found those who had been practicing yoga meditation for 5 years or more to have significantly lower baseline heart rates than those who with no meditation experience. 96 Of those clinical trials demonstrating positive effects, yoga practice was associated with a 3.8 to 60.3% reduction in respiratory rate and a 4.3 to 38.8% decline in heart rate ( Table 5).…”
Section: Effects Of Yoga On Markers Of Sympathetic/parasympathetic Acmentioning
confidence: 99%
See 2 more Smart Citations
“…98,115,125,127 These trials included studies of healthy ¶ ¶ and hypertensive adults 107,123 and of healthy children. 115,141 In addition, in a cross-sectional study of healthy middle-aged men, Vyas and colleagues found those who had been practicing yoga meditation for 5 years or more to have significantly lower baseline heart rates than those who with no meditation experience. 96 Of those clinical trials demonstrating positive effects, yoga practice was associated with a 3.8 to 60.3% reduction in respiratory rate and a 4.3 to 38.8% decline in heart rate ( Table 5).…”
Section: Effects Of Yoga On Markers Of Sympathetic/parasympathetic Acmentioning
confidence: 99%
“…Seven studies (of 8 total) have documented a 3.8% to 60.3% reduction in respiratory rate with yoga relative to baseline 103,104,116,139,140 and/or controls receiving usual care 123 or an aerobic exercise program 141 (Table 5). These investigations include studies in healthy adults 103,104,116,139,140 and children, 141 as well as in hypertensive adults. 123 Similarly, 21 of 24 total clinical trials reported a 4.3% to 38.8% decline in heart rate relative to baseline, engagement in a relaxing, nonyogic activity 104,[142][143][144][145] and/or controls receiving usual care, 123 an aerobic exercise program, 141 or no intervention.…”
Section: Effects Of Yoga On Markers Of Sympathetic/parasympathetic Acmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies involved adults; only 3 included children. 36,37,42 The sample sizes ranged from 10 to 158. Most studies had 20 -60 subjects, and only 5 studies had over 100.…”
Section: Samplesmentioning
confidence: 99%
“…Eleven studies focused on patients with respiratory disorders: COPD, 38,41,43,45,51,52,72,75 asthma 42,47 and pleural effusion. 48 Twenty-seven studied healthy people: older adults, 34,35,50,55,57,58,[60][61][62][63][64][65][73][74][75][76][77] healthy adults, 59 healthy males, 66,69 soldiers, 44 students, 46,53,71 children, 37 "residents," 59 and practitioners of tai chi/yoga. 56,67,68 The remaining 6 studies were on non-respiratory disorders (lower-limb disabilities, 70 breast cancer patients, 54 heart disease, 49 impaired vision, 36 Parkinson's disease, 40 and hypertension 39 ) but also measured respiratory outcomes.…”
Section: Samplesmentioning
confidence: 99%